Feminist Praxis Revisited: Critical Reflections on University-Community Engagement - Jennifer Musial (Atlantis)
Book under review: Dean, Amber, Johnson, Jennifer L., and Susanne Luhmann, eds. 2019. Feminist Praxis Revisited: Critical Reflections on University-Community Engagement. Waterloo: Wilfred Laurier Press.